2022
DOI: 10.1109/access.2022.3199690
|View full text |Cite
|
Sign up to set email alerts
|

Modeling-Eliciting Activities in an Online Engineering Course for Improving Conceptual Learning, Professional Skill, Interaction

Abstract: This empirical research aims to propose and examine an online teaching approach that embeds modeling-eliciting activities (MEA). The approach guides teachers to create a well-interactive online learning environment and improve the conceptual learning and professional skills of engineering undergraduates. The professional skills are defined as critical thinking and collaboration. A structured teaching procedure was implemented sequentially by task introduction, problem description, performance analysis, structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Research has identified the powerful functions of MEAs in STEM education as follows: 1) instructional tools for effective learning by supporting the development of metacognitive abilities and conceptual understanding [6], [29], [30], [31], [32], [33], [34], [35]; 2) robust authentic assessment tools for learning and teaching, providing instructors with a medium to identify and analyze students' thought processes while solving problems, as well as to assess their actual teamwork process [16], [26], [36]; and 3) tools for effective professional development to promote and improve knowledge for teaching and to shift a teaching philosophy to a more student-centered perspective [14], [37], [38], [39].…”
Section: B Model-eliciting Activities (Meas)mentioning
confidence: 99%
See 4 more Smart Citations
“…Research has identified the powerful functions of MEAs in STEM education as follows: 1) instructional tools for effective learning by supporting the development of metacognitive abilities and conceptual understanding [6], [29], [30], [31], [32], [33], [34], [35]; 2) robust authentic assessment tools for learning and teaching, providing instructors with a medium to identify and analyze students' thought processes while solving problems, as well as to assess their actual teamwork process [16], [26], [36]; and 3) tools for effective professional development to promote and improve knowledge for teaching and to shift a teaching philosophy to a more student-centered perspective [14], [37], [38], [39].…”
Section: B Model-eliciting Activities (Meas)mentioning
confidence: 99%
“…In particular, research is progressively documenting the success of MEAs as educational tools across a range of fundamental engineering subjects, including computer science, thermodynamics, materials, mechanical, chemical, electrical, industrial, and civil engineering [6], [8], [12], [13], [14], [15], [16], [40]. MEAs have proven effective in helping engineering students become better problem solvers by elevating their skills in problem-solving, modeling, and decision-making.…”
Section: B Model-eliciting Activities (Meas)mentioning
confidence: 99%
See 3 more Smart Citations